Konsepsi Kebahagiaan Lansia di Panti Wredha Harapan Ibu Ngaliyan Semarang - Sri Nugraheni Koespratiwi; Afidatul Lathifah; Amirudin Amirudin (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
The increase in the number of elderly people living who lived in nursing homes reflects that many elderly people are neglected and not taken care of by their families so that they run into problems with themselves as a result of feelings of lonely, loneliness and excile from their families affected their happiness degradation. The inability of the elderly to take care of and be responsible for themselves has encouraged Yayasan Dharma Wanita Persatuan Kota Semarang to address this problem. The solution of this problem is by established the Panti Wredha Harapan Ibu. . Based on research results, proved that most of the elderly feel happy living in a nursing home and interpret the concept of happiness with the feeling of joy that shown when they running their daily activities. The existence of these various services also makes the elderly at the Panti Wredha Harapan Ibu feel happy because all their life needs are fulfilled and guaranteed, they have many friends, and also do not have to think about living expenses, such as paying rent and paying for other necessities.